Video Analytics On Social Distancing And Detecting Mask - et. al., S. Jayashri, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
During this pandemic circumstance of Covid-19, social removing has become a standard general wellbeing mediation around the globe. Through social separating, wearing the face mask and try not to be in the group can slow the spread of Covid-19 illness. This survey is focused to inspect whether the people in a public maintains social distancing. It also checks whether every individual is wearing face mask. If both are not done, an alert is given to the public for maintain the social distance and it detect whether the individual is wearing mask or not. Applying deep learning algorithm to maintain social distancing in public place through video analytics technology.